Plan de negocios para la creación de un centro de capacitación online en la ciudad de Latacunga - Quevedo Ante, Angie Nathalia (2023)
The present work of a business plan for the creation of an online training company for applicants to the higher education system presented different stages, the business idea was carried out where the needs of potential clients were determined. The Market plan allowed to determine the different segmentations, identify the different policies of the product, price, place and promotion of the training service to the applicants to obtain a place in a higher education institution. Finally, with the financial plan it was possible to determine the feasibility of the business, with an investment of 48,350 dollars with 57% own capital and 42.42% onerous money, three courses of twelve participants are projected every three months, the price of the service is approximately $400.00.